2006
DOI: 10.1016/j.socscimed.2006.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Social environment and depression among pregnant women in urban areas of Pakistan: Importance of social relations

Abstract: Aspects of the social environment, including social conditions (socio-economic status, household situations, chronic illnesses) and social relations (attitude and behaviors of relations) are major determinants of depression among women. This study evaluates the relative power of social relations and social conditions in predicting depression among pregnant women in Pakistan. In the qualitative phase of the study, social environmental determinants were identified through literature search, and experts' opinions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
66
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 32 publications
10
66
0
1
Order By: Relevance
“…The increase of responsibilities and dependency from husband or partner, the work overload, and the lack of time for themselves might be some of the factors associated with depression in pregnant housewives. Nevertheless, our finding confirms the data of previous articles that found that household work was associated with depression in pregnant 23,24 and in nonpregnant women. 29 The women more vulnerable to minor depression were also those who previously experienced a depressive episode, as suggested by other studies, 3,4,18 and those who did not plan pregnancy, as reported by previous studies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The increase of responsibilities and dependency from husband or partner, the work overload, and the lack of time for themselves might be some of the factors associated with depression in pregnant housewives. Nevertheless, our finding confirms the data of previous articles that found that household work was associated with depression in pregnant 23,24 and in nonpregnant women. 29 The women more vulnerable to minor depression were also those who previously experienced a depressive episode, as suggested by other studies, 3,4,18 and those who did not plan pregnancy, as reported by previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…Our study suggests that a problematic relationship with the husband or partner represents an additional stress, which reduces the possibility of women adequately managing pregnancy and confirms the data of previous studies that observed that marital satisfaction protected against depression during pregnancy. 4,9,[21][22][23][24][25] Concerning minor depression, minor depression was diagnosed in 18% of women. Even though our finding confirms the prevalence of minor depression found in the general population 26,27 and in a recent study 19 investigating antenatal depression with the PRIME-MD, our data are higher than the best estimation of prevalence of minor depression in pregnancy observed in previous prospective studies (5.7%).…”
Section: Discussionmentioning
confidence: 99%
“…5 Another study in Pakistan showed, prevalence of depression, based on the cut-off score of 16 or more on CES-D scale, was 39.4%. 6 Majority of women with EPDS score more than 10 were in the age group above 30 years and in 3rd trimester of pregnancy. Increasing biological age has been found to be associated with increased depression.…”
Section: Discussionmentioning
confidence: 97%
“…Similar findings were observed after the 2008 earthquake in China (Kun et al, 2009b), which showed that social support is one of the important factors in predicting PTSD. In the context of Pakistan, a woman's relationship with her husband is an important aspect of women's mental health (Kazi et al, 2006). Further, a lack of socioeconomic autonomy increases women's risk for poor mental health (Patel et al, 2006b).…”
Section: Discussionmentioning
confidence: 99%